Health-related quality of life (HRQoL) and associated factors among pregnant women attending the Maternal and Child Health Clinic at the Government Hospital - Dahal, Tulasha; Neupane, Saraswati (Journal of Biratnagar Nursing Campus, 2025)
Background: Changes during pregnancy occur in physical, mental, spiritual and social dimensions and in all aspects of quality of life. However, less attention has been paid to mothers’ health. The Short Form 36 Health Survey Questionnaire (SF-36) is used to assess health-related quality of life and associated factors among pregnant women. Although quality of life plays an important role in the health of pregnant women, few studies have been conducted in Nepal. Methods: A cross-sectional quantitative study design was used. The data were collected via an interview schedule with a structured SF-36 questionnaire. Data entry and analysis were performed via a statistical software package for social sciences version 16. Descriptive statistics such as frequencies and proportions were used to describe the data. Bivariate analysis and multivariate analysis were used to assess the associations between the outcome variable and each independent variable. Results: The results revealed that the mean age of the women was 24.64±3.8 years and 94.5% of the women had high health-related quality of life. According to the bivariate analysis, among the 293 respondents, the level of HRQL was significantly associated with ethnicity (p=0.046) in the general health domain, the durations of pregnancy (p=0.014), employment (0.042), and type of family (0.024) were significantly associated with the physical activity domain, respectively. According to the multivariate analysis, religion (0.046), duration of pregnancy (0.019), and education (0.016), and duration of pregnancy (0.009) were associated with vitality and social functioning domains, respectively. Similarly, the duration of pregnancy (0.037) was associated with role-limiting emotional health, and economic status (0.029) and duration of pregnancy (0.023) were significantly associated with mental health. Therefore, the duration of pregnancy is a common factor in all domains. Conclusion: Pregnant women, who are in their second trimester, had a primary level education and a higher economic status, and had good HRQoL. Women who achieve primary-level education are associated with mental health, vitality and social functioning. This study will help plan maternal and child care, as well as help policymakers and health care providers to understand the necessity of such care and improve the quality of life of pregnant women.